Menilik Tantangan dan Strategi Pendidikan Luar Sekolah Berbasis Masyarakat - Sukari, Sukari; Ahmadi, Fauzan (TSAQOFAH, 2024)
Community-based out-of-school education has emerged as a strategic alternative to improve access to education, especially for communities underserved by the formal education system. Despite its great potential, it faces various challenges, including lack of government support, limited resources and negative stigma. This article aims to identify the meaning, forms, challenges and strategies to improve the effectiveness of community-based out-of-school education. The research method used in this study uses the library research method, which is research based on processed manuscripts (manuscript studies), facts and primary and secondary data (supporting data) related to the focus of the research, namely on community-based out-of-school education. To analyze the manuscript by using the content analysis approach, and questioning the content of the manuscript with experts in their fields. The result of this research is that there are several challenges in implementing community-based out-of-school education. Among them are lack of government support, limited resources, lack of public awareness, negative stigma, lack of collaboration, and challenges in evaluation. Therefore, collaboration between various parties and effective strategies are needed to increase participation and quality of out-of-school education, so that it has a positive impact on society.